PENGARUH IMPLEMENTASI SISTEM LAYANAN ONLINE KEPENDUDUKAN (SILOKA) TERHADAP OPTIMALISASI KUALITAS PELAYANAN ADMINISTRASI KEPENDUDUKAN - Pratidina, Ginung; Maulinda, winda; Apriliyani, Neng Virly; Salbiah, Euis (Jurnal Governansi, 2024)
The obstacles often faced by people in processing the population documents were long queues and limited quotas provided by DISDUKCAPIL of Bogor Regency. This impacted on a less optimal assessment of the service quality. The application of SILOKA became a prime strategy implemented by DISDUKCAPIL of Bogor Regency in providing population administration services. The main goal of implementing SILOKA was to facilitate people in registering population administration by online. This research aimed to examine the influence of the implementation of SILOKA on optimizing the quality of population administration services in DISDUKCAPIL of Bogor Regency. This research used associative quantitative method, involving 100 respondents as samples. Data were collected by questionnaires, interviews, and observations, and analyzed by Spearman rank correlation. Result of this research indicated coefficient correlation 0,848. It meant that there was a positive and significant correlation between the implementation of SILOKA and the quality of population administration services. The population administration services could be improved by implementing SILOKA in online queue collection procedures. The accomplishment was contributed by the capacity of implementing SILOKA in shortening the waiting times in order to fulfill the goal of the program and increase the people satisfaction on the population administration services by DISDUKCAPIL of Bogor Regency.